1988
DOI: 10.1180/claymin.1988.023.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxide impurity phases and distribution of structural iron in some diagenetic illitic clays as determined by Mössbauer spectroscopy

Abstract: Seven diagenetic illitie clays have been investigated by Mössbauer spectroscopy to characterize the forms of iron. Four specimens had measurable amounts of iron oxide impurity phases, accounting for up to ∼95% of the total Fe. Goethite, microcrystalline and probably aluminous, was identified as the oxide phase in three of these samples, the other containing hematite. This latter sample was also the only one which had tetrahedral Fe(III). Five of the samples contained measurable amounts of Fe(II), but the alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…This problem becomes particularly evident when Fe-poor illites are studied. Recent Mrssbauer work on illitic clays by Goodman & Nadeau (1988) and Wagner et al (1988 has shown that the presence of such ancillary constituents may render the study of illitic clays of little relevance to the parameters of illite sensu stricto. Possible remedial measures are the removal of undesired components by particle-size fractionation (provided different particle-size fractions differ sufficiently in mineralogy) or by selective dissolution (e.g.…”
mentioning
confidence: 99%
“…This problem becomes particularly evident when Fe-poor illites are studied. Recent Mrssbauer work on illitic clays by Goodman & Nadeau (1988) and Wagner et al (1988 has shown that the presence of such ancillary constituents may render the study of illitic clays of little relevance to the parameters of illite sensu stricto. Possible remedial measures are the removal of undesired components by particle-size fractionation (provided different particle-size fractions differ sufficiently in mineralogy) or by selective dissolution (e.g.…”
mentioning
confidence: 99%